Glacial history of the upper Drac Blanc catchment (French Alps) ... - Hofmann, Felix Martin (Albert-Ludwigs-Universität Freiburg, 2018)
Glacier advances in the Écrins massif (French Alps) during the Late Glacial and the Early Holocene are poorly constrained. Based on field observations, a high-resolution digital elevation model and an orthophoto, glacial landforms in the upper Drac Blanc catchment were mapped. Thanks to 42 new 10Be exposure ages, the timing of the stabilisation of selected moraines was constrained. The application of the accumulation area ratio method with a ratio of 0.67 enabled the determination of the Equilibrium Line Altitude (ELA) during the corresponding glacier advances and the amount it lowered compared to the end of the Little Ice Age. The lowermost sampled moraine may have been reached by a first glacier advance at around 16.9 ± 1.6 ka. Not unexpectedly, multiple moraines in the upper Drac Blanc catchment stabilised during Greenland stadial 1 and in the Early Holocene. During the furthest glacier advance somewhat before 12.5 ± 0.6 ka, a prominent moraine was shaped or, alternatively, re-occupied. The 10Be exposure ...